2019
DOI: 10.1093/imrn/rnz140
|View full text |Cite
|
Sign up to set email alerts
|

Poly-ℤ Group Actions on Kirchberg Algebras I

Abstract: This is the second part of our serial work on the classification of poly-Z group actions on Kirchberg algebras. Based on technical results obtained in our previous work, we completely reduce the problem to the classification of continuous fields of Kirchberg algebras over the classifying spaces. As an application, we determine the number of cocycle conjugacy classes of outer Z n -actions on the Cuntz algebras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…This deep theorem states that Kirchberg algebras are completely classified by KK-theory. This motivates further study on Kirchberg algebras, especially on their symmetrical structure and inclusions (see e.g., [41], [23], [24], [26]). We point out that this subject also has a strong connection to the index theory (see e.g., [21], [22]).…”
Section: Introductionmentioning
confidence: 97%
“…This deep theorem states that Kirchberg algebras are completely classified by KK-theory. This motivates further study on Kirchberg algebras, especially on their symmetrical structure and inclusions (see e.g., [41], [23], [24], [26]). We point out that this subject also has a strong connection to the index theory (see e.g., [21], [22]).…”
Section: Introductionmentioning
confidence: 97%
“…Results of Matui [14,15] and Izumi-Matui [11] have previously shown that the above is true for Z d -actions on all the known strongly self-absorbing C *algebras except for the Jiang-Su algebra Z. Sato [22] has shown such a uniqueness for Z-actions on Z, and Matui-Sato [16] have extended this also to Z 2 -actions on Z. We note that the uniqueness for actions of the Klein bottle group Z ⋊ −1 Z is also known by further work of Matui-Sato [17] on UHF algebras as well as Z; this was the first classification result for actions of non-abelian infinite groups on stably finite C * -algebras.…”
mentioning
confidence: 99%
“…It seems natural to expect that the known uniqueness results for Z dactions from [14,15,11] could be reproved abstractly within the common framework of semi-strongly self-absorbing actions, and without requiring the UCT assumption. It also seems plausible that this should in fact be possible for not necessarily abelian acting groups.…”
mentioning
confidence: 99%
“…Roughly speaking, a tensorial factorization of the form A ∼ = A ⊗ D -for a given C *algebra A and a strongly self-absorbing C * -algebra D -provides sufficient space to perform non-trival manipulations on elements inside A, which often gives rise to structural properties of particular interest for classification. The underlying motivation behind [82,83,80] is the idea that this kind of phenomenon should persist at the level of C * -dynamics if one is interested in classification of group actions up to cocycle conjugacy; in fact some much earlier work [55,56,40,29,63,65,39] has (sometimes implicitly) used this idea to reasonable success. It was further demonstrated in [80,81] how this approach can indeed give rise to new insights about classification or rigidity of group actions on certain C * -algebras, in particular strongly self-absorbing ones.…”
Section: Introductionmentioning
confidence: 99%
“…Initially appearing in works of Herman-Jones [30] and Herman-Ocneanu [31], the Rokhlin property for single automorphisms and its applications for classification were perfected in works of Kishimoto and various collaborators [8,50,5,52,21,53,54,18,6,68]. Further work pushed these techniques to actions of infinite higher-rank groups as well [67,44,60,61,62,40,39]. The case of finite groups was treated in work of Izumi [37,38], where it was shown that such actions with the Rokhlin property have a particularly rigid theory; see also [75,28,22,23,24,1,2].…”
Section: Introductionmentioning
confidence: 99%